(untitled) (Research, Society and Development, 2021)
The objective of the present work was to develop and characterize different formulations of chickpeas vegan hamburger with ora-pro-nóbis addition and verify the products acceptability. In this work, four formulations were developed with different proportions of chickpea (Cicer arietinum L.) and ora-pro-nóbis (Pereskia aculeata Mill): Formulation 1 (100% chickpeas), Formulation 2 (95% chickpeas and 5% ora-pro-nóbis), Formulation 3 (90% chickpeas and 10% ora-pro-nóbis) and Formulation 4 (85% chickpeas and 15% ora-pro-nóbis). Analyzes of proximal composition: moisture, proteins, fibers, lipids, ashes and carbohydrates, energetic value, as well as analyzes of water activity, total titratable acidity, pH and color parameters of raw hamburgers and ora-pro-nóbis leaf carried out. As well as sensory analysis, by the hamburguer acceptance test and purchase intention. The addition of ora-pro-nóbis leaves in the formulations resulted in moisture content and Aw increase, without altering the total titratable acidity and pH. In relation of color parameters, higher percentages of ora-pro- nóbis in the formulations reduced the hamburguers luminosity (decrease of L*), the red color (decrease of a*) and yellow color (decrease of b*). About sensorial analyses, it was verified that the samples with the heist score for attributes were F1 and F3. Considering the results, the hamburger with addition of 10% of ora-pro-nóbis leaves was the most accepted suggesting higher commercialization potential.